Feasibility of diesel-electric hybrid drives for combine harvesters - Good, Grant (Kansas State University, 2013)
Efficiency and technology are increasingly important selling points for combine harvesters. Diesel-electric hybrid drives have taken hold in the construction equipment industry, and are providing marketable efficiency benefits for some heavy equipment customers. This thesis explores the technical and economic feasibility of utilizing diesel-electric hybrid drives on AGCO combine harvesters. To determine the technical feasibility of utilizing diesel-electric hybrid drives on AGCO combine harvesters, a search was conducted for prior literature relating to the use of electric drives on other heavy, off-highway equipment. This information, coupled with data provided by experts in the field, was used to determine if electric drives could fulfill the unique requirements of combine harvesters, and be practically utilized for this application. To determine the economic feasibility of utilizing diesel-electric hybrid drives on AGCO combine harvesters, an optimization model was constructed to seek out the most economically viable configuration of electric drives for this application. The model takes in to consideration the different use-cases in which this equipment is expected to perform, as well as the component costs and operating efficiencies of both the drives in place currently and the proposed electric drives. The outcome of the model was then utilized to compare the best-case configuration to the minimum requirement for economic feasibility. The technical feasibility assessment conducted for this thesis led to the conclusion that it would be technically feasible to utilize electric drives on a combine harvester. There are commercially available electric drive components which are suitable for use in the environment that this equipment is expected to operate in, and a prototype combine harvester having electric drives has previously been constructed. The economic feasibility assessment conducted for this thesis revealed that it is not economically feasible to utilize electric drives on AGCO combine harvesters at this time. Under the current circumstances, the most economically viable configuration would take nearly twice the machine’s usable operating life to provide a benefit to a customer from fuel savings. Sensitivity analysis revealed that significant changes in the price of fuel or electric drive components would be necessary to change the outcome of this study.
Keywords: Electric drives; Combines; Fuel efficiency; Break-even; Economics, Agricultural (0503); Mechanical Engineering (0548)